SERTIFIKASI MINYAK SAWIT PETANI: DAMPAK TERHADAP PEMBANGUNAN DAN PENGHIDUPAN BERKELANJUTAN - Chalil, Diana; Sidique, Shaufique F; Barus, Riantri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
Sustainable palm oil certification is expected to lead to sustainable development and livelihood. This study was conductedthrough 240 and 176 certified and non-certified oil palm smallholders in Indonesia and Malaysia, respectively. The data were collected using theclustered convenience sampling method and analyzed with compare means test. The results show that certified smallholders have a superiorperception and implementation of a sustainable economic and socialenvironment, enjoy higher productivity and selling prices, are able to maintain the quality of natural resources,are more resistant toproduction and price fluctuations, and are more prepared for replanting.